2022
DOI: 10.15408/sjie.v11i1.20280
|View full text |Cite
|
Sign up to set email alerts
|

The Flip Side of Economic Growth – Predictions from Indonesia

Abstract: Special attention in the future will emphasize patterns or studies thatare relevant and new in highlighting sustainable economic growth. Weseek to identify the role of factors outside of fiscal and monetary policyon economic growth in Indonesia, such as happiness, demographicpressures, labor force, and human development. For this purpose,the OLS method has presented time-series data (2015-2019).Prediction studies show that happiness, demographic pressures, andhuman development can increase economic growth in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
3
0
2
Order By: Relevance
“…It is often misunderstood that economic freedom will erode plural welfare because it rests on individual freedom, which is rooted in ideological prejudices that oppose freedom, and equality, where abundant facts show that the interval of economic freedom is directly proportional to the increase in social welfare (Näsström, 2021). This welfare is not only focused on the economic aspect but also on the health and education aspects (Irwansyah et al, 2022).…”
Section: Economic Freedommentioning
confidence: 99%
“…It is often misunderstood that economic freedom will erode plural welfare because it rests on individual freedom, which is rooted in ideological prejudices that oppose freedom, and equality, where abundant facts show that the interval of economic freedom is directly proportional to the increase in social welfare (Näsström, 2021). This welfare is not only focused on the economic aspect but also on the health and education aspects (Irwansyah et al, 2022).…”
Section: Economic Freedommentioning
confidence: 99%
“…Berbicara premis pembangunan manusia yang komprehensif, tidak selalu ditentukan oleh unsur materi ataupun sistem pendataan yang didasarkan pada finansial, yang tentu bisa dengan mudah dikalkulasi, diakumulasi, dan terlacak. Ambil contoh standar pada kebahagiaan dan inovasi, dimana kedua pilar ini lebih menonjolkan lingkungan tempat tinggal, sosial, fasilitas, infrastruktur, keamanan, institusi, kecanggihan adaptasi teknologi, karakteristik budaya, dan banyak unsur lainnya yang terlibat (Fitriadi et al, 2022;Irwansyah et al, 2022;Wijaya et al, 2021;ZA et al, 2021). Dari preferensi yang ada, menuju produktivitas penduduk yang disiratkan oleh pembangunan manusia dapat dibedah dalam ruang yang holistik.…”
Section: Pendahuluanunclassified
“…Second, there is a difference in place utility from one location to another. Irwansyah et al (2022) and Wijaya et al (2021) concluded that, in Romania, demographic pressures are integrated into economic growth; in developing countries like Indonesia, demographic pressures control the GDP.…”
Section: Demographic Theoriesmentioning
confidence: 99%